Resolving the taxonomic status of biocontrol agents belonging to the Aphidius eadyi species group (Hymenoptera: Braconidae: Aphidiinae): an integrative approach - Petrović, A; Mitrović, M; Ghaliow, M E; Ivanović, A; Kavallieratos, N G; Starý, P; Tomanović, Ž (Bulletin of entomological research, 2019)
Species that belong to the Aphidius eadyi group have been used as biocontrol agents against Acyrthosiphon pisum worldwide. However, despite their extensive use, there are still gaps in our knowledge about their taxonomy and distribution. In this study, we employed an integrative taxonomic approach by combining genetic analyses (mtDNA COI barcoding) with standard morphological analyses and geometric morphometrics of forewing shape. We identified three species within the A. eadyi species group, viz., A. smithi, A. eadyi and A. banksae. Genetic separation of all three species was confirmed, with mean genetic distances between species ranging from 5 to 7.4%. The following morphological characters were determined as the most important for separating species of the A. eadyi group: number and shape of costulae on the anterolateral part of the petiole, shape of the central areola on the propodeum, and shape and venation of the forewings. The differences in wing shape of all three species were statistically significant, but with some overlapping. We identified A. banksae as a widely distributed pea aphid parasitoid, whose known range covers most of the western Palaearctic (from the UK to Israel). Aphidius banksae is diagnosed and redescribed.
Keywords: Wasps; mitochondriální DNA; DNA, Mitochondrial; zvířata; Aphids; druhová specificita; Wings, Animal; mužské pohlaví; Species Specificity; DNA Barcoding, Taxonomic; sršňovití; křídla zvířecí; biologická ochrana; mšice; ženské pohlaví; Biological Control Agents; Animals; Male; taxonomické DNA čárové kódování; Female